2016
DOI: 10.1177/1533034615618849
|View full text |Cite
|
Sign up to set email alerts
|

MiR-125b Functions as a Tumor Suppressor and Enhances Chemosensitivity to Cisplatin in Osteosarcoma

Abstract: Copyright: Zhang et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. ABSTRACT Numerous studies have shown drug resistance of gastric cancer cells could be modulated by abnormal expression of microRNAs. Cisplatin (DDP) is one of the most commonly used drugs for chemotherapy of gastric cancer. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 31 publications
(35 reference statements)
3
33
0
Order By: Relevance
“…26-29 miR-125b functions as a tumor suppressor in ovarian cancer, breast cancer, osteosarcoma and bladder cancer. [26][27][28][29][30][31][32] However, in prostate cancer, glioma and leukemia, miR-125b functions as an oncogene by targeting tumor suppressors. [33][34][35] miR-143-3p, miR-145-5p and miR-145-3p are clustered on chromosome 5q32, and multiple signatures have shown that these miRNAs are downregulated in BC.…”
Section: Downregulated Mirnas In Multiple Bc Signaturesmentioning
confidence: 99%
“…26-29 miR-125b functions as a tumor suppressor in ovarian cancer, breast cancer, osteosarcoma and bladder cancer. [26][27][28][29][30][31][32] However, in prostate cancer, glioma and leukemia, miR-125b functions as an oncogene by targeting tumor suppressors. [33][34][35] miR-143-3p, miR-145-5p and miR-145-3p are clustered on chromosome 5q32, and multiple signatures have shown that these miRNAs are downregulated in BC.…”
Section: Downregulated Mirnas In Multiple Bc Signaturesmentioning
confidence: 99%
“…Growing evidence indicates that various miRNAs (including miR-92a, miR-99b, miR-132, miR-193a-5p, miR-422a, and miR-125b) are involved in the development of resistance to chemotherapy [5], [9], [10]. It is thought that miR-125b can act as both an oncogene and a tumor suppressor, depending on the cellular context [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies about miR-125b indicated that miR-125b acted as a tumor suppressor in osteosarcoma, ovarian cancer, hepatocellular carcinoma (HCC) and gastric cancer (15,(24)(25)(26). In ovarian cancer, miR-125a and miR-125b could inhibit ovarian cancer cell migration, invasion and proliferation by regulating EIF4E-binding protein 1 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miR-125b may be used as a biomarker for gastric cancer (26). Wang et al (15) revealed that tumor suppressive miR-125b could negatively regulate osteosarcoma cell proliferation, invasion and migration, and that overexpression of miR-125b enhanced the chemosensitivity of osteosarcoma cells to cisplatin by targeting Bcl-2. Another study revealed that low expression of miR-125b in osteosarcoma predicted a poor prognosis (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation